Prediction of Long-Term Prestress Loss and Crack Resistance Analysis of Corroded Prestressed Concrete Box-Girder Bridges - Yiming Yang; Huang Tang; Yu Mao; Xinzhong Wang (Advances in Civil Engineering)
Reasonable assessment of long-term prestress loss and crack resistance is essential to ensure the service performance of prestressed concrete (PC) bridges. In this paper, a novel prediction model of long-term prestress loss considering the coupling effect of shrinkage and creep of concrete, prestressing steel relaxation, and presence of nonprestressing steel as well as the corrosion of prestressing and nonprestressing steel is proposed. Then, the probability analysis approach of long-term prestress loss considering the uncertainties of calculation parameters and models is introduced. Moreover, the assessment approach of crack resistance of local and overall structure is also developed, taking into account the effect of corrosion and time-dependent long-term prestress loss. The previously proposed approaches are applied to a three-span PC box-girder bridge. It is found that the prediction results of long-term prestress loss have high uncertainty, and the upper bound of long-term prestress loss at the confidence level of 95% is approximately 50% higher than the result obtained by deterministic analysis. The effect of corrosion on the long-term prestress loss is basically negligible, and the crack resistance of bottom slab and web is more sensitive to the coupled effect of corrosion and long-term prestress loss than that of top slab. Additionally, setting vertical prestressing tendons is conducive to improving the crack resistance level of web and whole section.